KORELASI ANTARA PENGALAMAN BERNYANYI PADA KEGIATAN IBADAH ROHANI TERHADAP HASIL BELAJAR BERNYANYI DI SMP KRISTEN KALAM KUDUS PADANG - Novi Satria Pahlawanti Zalukhu; Jagar Lumbantoruan; Yensharti Yensharti (FBS Universitas Negeri Padang, 2018)
Abstract This study aimed to determine whether there was a correlation of singing spiritual worship at school services to the results of singing learning in SMP Kristen Kalam Kudus Padang and found out how much the correlation of singing spiritual worship to the results of singing learning. This research used a quantitative research method with a correlation research type. The populations in this research were 22 students of class VII of Christian SMP Kalam Kudus Padang. Determination of the number of sample members in this study was done by taking 100% due to the number of small relatively population, less than 30 people using saturated sampling technique. The validity instruments were done by content validity test and correlation test. Data analysis technique used was product moment correlation statistic. The results of this study indicated that there was a positive correlation that was moderate and significant between singing spiritual worship at school devotion to the results of studying class VII students of SMP Kristen Kalam Kudus Padang academic year 2017-2018, it was proved from the value of the correlation coefficient greater than r table ( 0.563> 0.432) and a significance value of 0.006, which meant less than 0.05 (0.006 <0.05). The result of data analysis also showed the value of r2 equal to 0,317; the value meant that 32% changed in the variable of singing of spiritual worship at school services could be explained by the result of singing learning of the seventh grade of junior high school Christian Kalam Kudus Padang, while the rest 60,8% influenced by other variable were not examined in this research. Keyword: Singing, Spiritual Worship, Learning Outcomes, Correlation.